2019
DOI: 10.1111/1556-4029.14087
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of a Natural Fluorophore as a Key to Improve Fingerprint Contrast Image

Abstract: The optical and morphological properties of resveratrol were investigated. This nontoxic fluorescent natural material, emitting in the visible blue light, was used as an optical marker, enabling the enhancement of the image contrast coming from relief pictures marked on challenging surfaces. By applying appropriated imaging softwares, this marker was verified to be very useful in the latent fingerprint recognition deposited on different wood surface types, mainly those with high level of roughness, where conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These studies concentrated on the chemical imaging of fingermarks and spectrometry as can be observed on Figure 6. Considering the articles published with at least one author with Brazilian affiliation, the focus of the studies at the same period was the synthesis and applications of new fingerprint developers materials [3][4][5][6][7][8][9][10] . These studies aimed to identify low-cost materials, some based on natural resources, which presented greater contrast in different situations, such as dark backgrounds and metallic surfaces, when compared to traditional developers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies concentrated on the chemical imaging of fingermarks and spectrometry as can be observed on Figure 6. Considering the articles published with at least one author with Brazilian affiliation, the focus of the studies at the same period was the synthesis and applications of new fingerprint developers materials [3][4][5][6][7][8][9][10] . These studies aimed to identify low-cost materials, some based on natural resources, which presented greater contrast in different situations, such as dark backgrounds and metallic surfaces, when compared to traditional developers.…”
Section: Resultsmentioning
confidence: 99%
“…The study aimed to demonstrate that a developer agent, which can be synthesized, according to the principles of clean chemistry and can favor the cost reduction, can be used as an option instead of conventional ones, since traditional developers have high import costs and chemical components. The results were considered satisfactory due to the quality of the development of the fingerprint and the reduction of residues generated to the environment, also reducing the exposure of experts, although the method has limitations, such as the type of surface.A methodology based on the natural fluorophores fluorescence was studied by Oliveira et al10 to increase the contrast between the fingerprint and the background. For this, resveratrol (a low-cost, natural and non-toxic fluorescent substance) and photography techniques associated with UV light illumination (365 nm) were used to increase the contrast of the latent fingerprint deposited on a porous wooden surface.…”
mentioning
confidence: 99%
“…Preliminary/Pilot studies – Several compounds were presented as new dusting powders: AIE-active composites or molecules [ [277] , [278] , [279] , [280] , [281] ], algal biomass [ 282 ], anti-perovskite phosphors [ 283 ], azo-dyes [ 284 ], β-cyclodextrin-berberine complexes [ 285 ], benzazole derivatives [ 286 ], bisamide analogues [ 287 ], cadmium-doped silica microspheres [ 288 ], chitosan-tripolyphosphate-lysine conjugates [ 289 ], coumarin–pyridone conjugates [ 290 ], crushed eggshells and clamshells [ 291 ], crushed gambir [ 292 ], curcumin analogues [ 293 ], doped montmorillonite [ 278 , 294 , 295 ], doped starch microspheres [ [296] , [297] , [298] ], europium-dextrose composites [ 299 ], iron oxide/zinc sulphide hybrid [ 300 ], metal-organic frameworks [ 301 ], organic NIR emitters [ 302 , 303 ], perylenetetracarboxylate compounds [ 304 ], phenylthiazoles [ 305 ], phosphor-cellulose hybrids [ 306 ], pyrazoles [ 307 ], pyrene-tagged imidazolium salts [ 308 ], pyridine and pyrimidine derivatives [ 309 , 310 ], rare-earth-doped phosphors [ [311] , [312] , [313] , [314] , [315] , [316] , [317] , [318] , [319] ], reduced graphene oxides [ 320 ], resveratrol powder [ 321 ], rhodamine B-doped diatomaceous earth [ 322 ], Schiff base complexes [ [323] , [324] , [325] ], talcum powder […”
Section: Fingermark Visualisationmentioning
confidence: 99%